Effect of Finishing Protocol on Obtaining and Maintaining Gloss in Four Nanohybrid Resin Composites - Marín-Velasquez, Julissa; Osorio-Vélez, Laura; Lassila, Lippo; Ardila, Carlos M. (Cureus Inc, 2025)
Objective:
Within the clinical objectives of performing direct restorations with resin composites is the achievement of an optimal surface in mechanical terms, while also resembling the natural optical characteristics of dental enamel. The aim of this study is to compare the gloss levels achieved in four nanohybrid resins using four different finishing/polishing (F/P) protocols and assess the retention of gloss after an aging process.
Methods:
Forty-eight A2-colored samples from four commercial brands (Filtek Z250 XT, Tetric N-Ceram, Zafira, and Spectra Smart) were prepared, with 12 specimens per resin. The samples were divided into four subgroups based on the F/P treatment: T1 (clinical polishing sequence with ShapeGuard system), T2 (metallographic polishing sequence), T3 (clinical polishing sequence with PermaSeal), and T4 (final polymerization through glycerin and clinical polishing sequence). Gloss measurements were taken before and after aging. ANOVA one-way was done.
Results:
Before aging, Z250 showed the highest average gloss in T1 (77.2 gloss units - GU), while Zafira (43.8 GU), Tetric (39.5 GU), and Spectra (33.5 GU) had lower values. In T2, Zafira (92.7 GU) and Spectra (87.4 GU) had the highest average gloss, and Tetric (75.7 GU) and Z250 (78.3 GU) had the lowest. No significant differences were found in T3, and in T4, Z250 had the highest average gloss (78.9 GU), followed by Tetric (74.7 GU) and Zafira (52.5 GU), with Spectra having the lowest (42.7 GU). Control group gloss levels ranged from 61.8 to 71.8 GU and remained consistent after aging, except for Tetric in T1 (p=0.045).
Conclusions:
The impact of F/P strategies on gloss retention varies with the material, even within the same resin composite classification. The initial gloss level appears to be a more critical factor for long-term gloss retention than the specific F/P protocol used.